Evaluating the heading in professional soccer players by playing positions - Erkmen, N. (The Journal of Strength and Conditioning Research, 2009)
The aim of this study is to evaluate the accuracy and coordination of heading in professional soccer players of different positions. A total of 243 professional soccer players were examined for the study. The Federation Internationale de Football Association Medical Assessment and Research Center (F-MARC) test battery was used to evaluate heading in soccer players. In the heading of the ball thrown from middle of the goal, forwards were better than goalkeepers (p < 0.05). There was not a significant statistical difference between defenders, midfielders, and forwards. In the heading of the ball thrown from the right side of the goalpost, defenders were better than goalkeepers (p < 0.05) and forwards were better than goalkeepers, defenders, and midfielders (p < 0.05). In conclusion, the reason for the heading of goalkeepers being worse than the others; goalkeepers use their hands in both training and matches, whereas for forwards and defensive players being better than goalkeepers depends mainly on their positions in soccer. Trainers and coaches should give place specific training programs to improve heading ability in the training schedule of soccer players at a professional level.